Prevalence of Fasciola hepatica in Goats and Sheep by Using ELISA in Sera and Milk in Duhok, Iraq - Mikaeel, Farhad B. (The Iraqi Journal of Veterinary Medicine, 2020)
An indirect ELISA technique was used to determine the prevalence of infection in sera and milk samples among goats and sheepin Duhok, Kurdistan Region, Iraq. Results of the present study shows that the prevalence of infection was higher in sera compared to milk samples among goats and sheep as follow: (6.3, 4.2%) and (8.9, 5.6%) respectively and there was no statistical significance difference in goats at P value =0.42, also there was no statistically differences at P value= 0.22. ELISA results also shows that the prevalence according to the age among goats and sheep were higher in animal aged > 2 years in both sera and milk samples were (7.5, 5.3%) and (11.3, 7%) respectively and there was no significant difference between age groups of goats and sheep by ELISA. The present study is the first study done to determine the prevalence of F. hepatica in both sera and milk samples among local goats and sheep. Continuously screening of sheep and goats for Fascioliasis and using of anthelmintic to control the infection in small ruminants is necessary